Assessment of genetic variability and character association for yield improvement in sunflower (Bangladesh Journal of Botany, 2026)
Genetic variability and character association were studied in 45 sunflower genotypes to identify trait-specific variability for yield and yield related traits. Significant variation was found among genotypes for all traits. High genotypic coefficients of variation were observed for single plant yield, hundred seed weight, and head diameter. High heritability and genetic advance indicated the impact of additive gene action and promoting selection. Single plant yield positively correlated with head diameter, hundred seed weight, hull content, and plant height, but negatively with days to maturity. Principal component (PC) analysis identified three major components PC 1, 2 and 3 cumulative variation (68.96%) and these were only with eigenvalue greater than 1. The study indicates significant variability among the genotypes, which is valuable for identifying diverse genotypes through genetic diversity analysis and could be utilized as parents for sunflower yield improvement.Bangladesh J. Bot. 55(2): 363-369, 2026 (June)